Application of Sonic Tests and Modal Identification in the Characterization of Masonry Walls - Inês Bourgeois; Leandro Torres Di Gregorio; Hugo Rodrigues; Jorge Fonseca; Alice Tavares; Aníbal Costa (Applied Sciences, 2023)
This work contemplates the application of non-destructive techniques, sonic and environmental vibration tests, on a set of soil-cement compressed earth blocks reinforced masonry walls, which were built in laboratory, under the project SHS-Multirisk. The present work constitutes a comparative study that aimed at verifying the reliability of the sonic test method in masonry characterization and in testing a methodology of combined tests for structural assessment. For that purpose, a numerical model of the walls was developed and calibrated with the mechanical properties that were calculated from the sonic tests data. The results of the simulation of the numerical model were compared with the results of the environmental vibration tests, which enabled to reach a correlation between the frequencies, as well as enabling the indirect sonic tests, which were performed in the vertical direction, to result in an accurate prediction of the Young modulus to be used in the numerical models.